2021
DOI: 10.1007/s00705-021-05156-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021)

Abstract: This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2021. The entire ICTV was invited to vote on 290 taxonomic proposals approved by the ICTV Executive Committee at its meeting in October 2020, as well as on the proposed revision of the International Code of Virus Classification and Nomenclature (ICVCN). All proposals and the revision were ratified by an absolute majority of the ICTV members. Of note, ICTV mandated a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(183 citation statements)
references
References 14 publications
4
177
0
2
Order By: Relevance
“…We report here the identification and in-depth biological and molecular characterization of a new virus infecting non-cultivated Ligustrum vulgare in wild ecosystems, named ligustrum mosaic virus (LigMV). Based on the International Committee of Taxonomy of Viruses (ICTV)-species demarcation criterion based on complete genome sequence similarity, this 3-segmented + ssRNA virus should be considered as a first representative of a novel species in the genus Hordeivirus of family Virgaviridae (Adams et al, 2017;Savenkov, 2021), for which we propose a name Hordeivirus ligustri to conform a binomial nomenclature species format recently adopted by the ICTV (Walker et al, 2021). Erwin Baur, who described for the first time a viral mosaic disease in Ligustrum, reported that the virus could not be seedtransmitted (Baur, 1908).…”
Section: Discussionmentioning
confidence: 99%
“…We report here the identification and in-depth biological and molecular characterization of a new virus infecting non-cultivated Ligustrum vulgare in wild ecosystems, named ligustrum mosaic virus (LigMV). Based on the International Committee of Taxonomy of Viruses (ICTV)-species demarcation criterion based on complete genome sequence similarity, this 3-segmented + ssRNA virus should be considered as a first representative of a novel species in the genus Hordeivirus of family Virgaviridae (Adams et al, 2017;Savenkov, 2021), for which we propose a name Hordeivirus ligustri to conform a binomial nomenclature species format recently adopted by the ICTV (Walker et al, 2021). Erwin Baur, who described for the first time a viral mosaic disease in Ligustrum, reported that the virus could not be seedtransmitted (Baur, 1908).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Demovir [ 43 ] was applied to assign taxonomy to the vOTUs using default parameters. For those viral genomes that could not be identified and annotated by Demovir, vConTACT 2.0 was then used to annotate the remaining unknown sequences at the family level by manual curation of the network clusters using taxonomic information from the Master Species List (MSL36) [ 44 ]. If neither tool was able to assign taxonomy, the viral genomes were labelled as “unassigned”.…”
Section: Methodsmentioning
confidence: 99%
“…The Schitoviridae family encompasses some 120 N4-like bacteriophages with a genome organisation similar to the Escherichia phage N4. The family was recently proposed by Wittmann et al [147] and ratified by the ICTV in March 2021 [148]. Four bacteriophages infecting the Pectobacterium species are assigned to the genus of Cbunavirus of the Schitoviridae family in the ICTV Master Species List [149], but an analysis of the GenBank sequences indicates that more SRP phages can be assigned to the Schitoviridae family (Table 5).…”
Section: The Schitoviridae Familymentioning
confidence: 99%